Black Tea Polyphenols Inhibit Tumor Proteasome Activity - MUJTABA, TASKEEN (2012)
Tea is a widely consumed beverage and its constituent polyphenols have been associated with potential health benefits. Although black tea polyphenols have been reported to possess potent anticancer activities, the effect of its polyphenols, theaflavins on the tumor’s cellular proteasome function, an important biological target in cancer prevention, has not been carefully studied. Here black tea extract (T5550) enriched in theaflavins inhibited the chymotrypsin-like (CT) activity of the proteasome and proliferation of human multiple myeloma cells in a dose-dependent manner. Also an isolated theaflavin (TF-1) can bind to, and inhibit the purified 20S proteasome, accompanied by suppression of tumor cell proliferation, suggesting that the tumor proteasome is an important target whose inhibition is at least partially responsible for the anti-cancer effects of black tea.